A model with two inert scalar doublets - Machado, A. C. B. [UNESP]; Pleitez, V. [UNESP] (Elsevier B.V., 2016)
We consider an extension of the standard model (SM) with three SU(2) scalar doublets and discrete S-3 circle times Z(2) symmetries. The irreducible representation of S3 has a singlet and a doublet, and here we show that the singlet corresponds to the SM-like Higgs and the two additional SU(2) doublets forming a S-3 doublet are inert. In general, in a three scalar doublet model, with or without S-3 symmetry, the diagonalization of the mass matrices implies arbitrary unitary matrices. However, we show that in our model these matrices are of the tri-bimaximal type. We also analyzed the scalar mass spectra and the conditions for the scalar potential is bounded from below at the tree level. We also discuss some phenomenological consequences of the model. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Inert-doublets model; Dark-matter